Transport and assembly of gag proteins into Moloney murine leukemia virus. - Hansen, M (1990)
We have studied the process of Moloney murine leukemia virus (M-MuLV) assembly by characterization of core (gag) protein mutants and analysis of wild-type (wt) gag proteins produced by cells in the presence of the ionophore monensin. Our genetic studies involved examination of linker insertion mutants of a Gag-beta-galactosidase (Gag-beta-gal) fusion protein, GBG2051, which is incorporated into virus particles when expressed in the presence of wt viral proteins. Analysis indicated that the amino-terminal two-thirds of the gag matrix domain is essential for targeting of proteins to the plasma membrane; mutant proteins localized to the cytoplasm or were trapped on intracellular membranes. Mutations through most of the coding region of the gag capsid domain generated proteins which were released from cells in membrane vesicles but not in virions. In contrast, linker insertions into p12gag or carboxy-terminal portions of the matrix or capsid coding regions did not affect assembly of fusion proteins into virus particles. Monensin, which blocks vesicular transport, inhibited gag protein intracellular transport and release from cells. Our results suggest that a significant proportion of M-MuLV myristylated gag proteins travel via vesicles to the cell surface. Specific matrix protein polypeptide regions and myristic acid modification are both necessary for appropriate gag protein transport, while capsid protein interactions appear to mediate the final phase of virion formation.